Activation of glycine receptors modulates spontaneous epileptiform activity in the immature rat hippocampus - Chen, Rongqing (J Physiol, 2014)
While the expression of glycine receptors in the immature hippocampus has been shown, no information about the role of glycine receptors in controlling the excitability in the immature CNS is available. Therefore, we examined the effect of glycinergic agonists and antagonists in the CA3 region of an intact corticohippocampal preparation of the immature (postnatal days 4–7) rat using field potential recordings. Bath application of 100 μm taurine or 10 μm glycine enhanced the occurrence of recurrent epileptiform activity induced by 20 μm 4-aminopyridine in low Mg(2+) solution. This proconvulsive effect was prevented by 3 μm strychnine or after incubation with the loop diuretic bumetanide (10 μm), suggesting that it required glycine receptors and an active NKCC1-dependent Cl(−) accumulation. Application of higher doses of taurine (≥1 mm) or glycine (100 μm) attenuated recurrent epileptiform discharges. The anticonvulsive effect of taurine was also observed in the presence of the GABA(A) receptor antagonist gabazine and was attenuated by strychnine, suggesting that it was partially mediated by glycine receptors. Bath application of the glycinergic antagonist strychnine (0.3 μm) induced epileptiform discharges. We conclude from these results that in the immature hippocampus, activation of glycine receptors can mediate both pro- and anticonvulsive effects, but that a persistent activation of glycine receptors is required to suppress epileptiform activity. In summary, our study elucidated the important role of glycine receptors in the control of neuronal excitability in the immature hippocampus.